A symbolic-philosophical kawung batik–based mathematical mindset intervention in STEAM education: A conceptual design - Abdul Aziz Saefudin; Mahilda Dea Komalasari; R. Hafid Hardyanto; Erni Puji Astuti; Dian Putri Pramitasari; Diva Al Diniyah (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2025)
Research on the relationship between mathematical attitudes and cultural values is lacking, especially in non-Western educational contexts. This study proposes mindset interventions based on the philosophical and symbolic interpretations of Kawung Batik, a Javanese motif expressing harmony, resilience, self-reflection, and social connectivity. The methodology combines theoretical literature with a cultural-symbolic understanding of Kawung's relevance. Saefudin et al. (2023) identified six psychological dimensions of mathematical mindset: beliefs about ability, reactions to adversity, attitudes toward failure, appreciation of effort, openness to critique, and perceptions of peer success. The symbolic constructs are carefully aligned with these dimensions. The framework includes four STEAM pedagogical designs: reconstructing geometric shapes, algorithmically producing patterns, studying batik materials and processes, and critically reflecting on cultural significances. These scenarios stimulate emotional and cognitive development and promote a culturally integrated mathematical identity. The proposed methodology reframes culture as a powerful tool for transforming students' mathematics learning experiences. This study lays the groundwork for classroom-based research, including iterative design studies to confirm the model's pedagogical and affective effects.